Pendampingan Komunitas Lembaga Pendidikan Bahasa Arab dalam Pembelajaran Al-Mufradat melalui Media Flash Card di Lembaga Pendidikan Bahasa Arab (LPBA) Al-Qodiri Jember - Muhammad ‘Ainul Yaqin; Muhammad Yunus; Muhammad Risqi (GUYUB: Journal of Community Engagement, 2020)
This community service is to facilitate students in practicing Arabic vocabularies in everyday life. By using Asset Basic Community Development (ABCD) as an approach, this service resulted that making use of flash card media is important for helping students in increasing their mastery of Arabic vocabularies in Arabic Learning Institution (LPBA) at Al-Qodiri Jember. They can easily practice Arabic vocabularies by using flash cards. These cards could be carried anywhere either inside or outside the classroom. Using flash card media have been able to develop the positive athmosphere of the Arabic speaking environment in LPBA Al-Qodiri and in practicing Arabic vocabularies.